Diversity and antioxidant activity of endophytic fungi isolated from salam (Syzygium polyanthum) - HARY WIDJAJANTI; ELFITA ELFITA; MIA TIRTA SARI; NURLISA HIDAYATI; POEDJI LOEKITOWATI HARIANI; ARUM SETIAWAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Widjajanti H, Elfita, Sari MT, Hidayati N, Hariani PL, Setiawan A. 2023. Diversity and antioxidant activity of endophytic fungi isolated from salam (Syzygium polyanthum). Biodiversitas 24: 3051-3062. Salam (Syzygium polyanthum (Wight) Walp.) is a medicinal plant from the family Myrtaceae. The leaves are used as a spice and treat diseases such as diabetes mellitus, hypertension, ulcers, diarrhea, gastritis, and skin. This study aimed to determine endophytic fungi's diversity and antioxidant activity in the S. polyanthum plant. In addition, the distribution of endophytic fungi found on S. polyanthum was compared to that of previously reported endophytic fungi on other species of Syzygium. The distribution pattern of these endophytic fungi is needed to determine the presence of potential endophytic fungi that can live in host plants of the same genus. The endophytic fungi were isolated from fresh root bark, stem bark, and leaf tissues of S. polyanthum. The endophytic fungi were identified morphologically to determine their level of diversity; their extract was then tested for their antioxidant activity using the DPPH method. The extract that showed the highest antioxidant activity was identified molecularly. A total of 18 endophytic fungi were obtained from S. polyanthum, including seven isolates from root bark (HSA1–HSA7), four isolates from stem bark (HSB1–HSB4), and seven isolates from leaves (HSD1–HSD7). The morphological identification showed seven genera scattered in all investigated parts: Trichoderma, Penicillium, Aspergillus, Pythium, Papulaspora, Pythiogeton, and Clonostachys. The HSD5 isolate showed the best antioxidant activity, and the molecular identification confirmed this isolate as Clonostachys rosea. The comparison of the distribution of endophytic fungi isolated from S. polyanthum to endophytic fungi isolated from the host genus Syzygium showed that endophytic fungi of three genera, namely Clonostachys, Papulaspora, and Pythiogeton, are specifically found on S. polyanthum. In addition, those of four other genera, namely Trichoderma, Aspergillus, Penicillium, and Pythium, are found on other species of Syzygium.